Management of bile leak following blunt liver injury: a proposed guideline. Issue 6 (18th January 2021) - Oo, June; Smith, Marty; Ban, Ee Jun; Clements, Warren; Tagkalidis, Peter; Fitzgerald, Mark; Pilgrim, Charles H. C.
Abstract: Background: Bile leak following blunt liver trauma is uncommon. Management is difficult due to complex vasculo‐biliary and liver parenchymal injury and lack of consensus on optimal care compared with bile leak following elective hepatectomy especially in regards to endoscopic retrograde pancreaticocholangiography (ERCP) timing and patient selection. Methods: This is a retrospective cohort study from a level 1‐trauma centre of patients with bile leak following blunt liver injury between July 2010 and December 2019 identified from the trauma registry. Clinical data retrieved include patient demographics, injury severity score, liver injury grading and its associated complications and treatment. This was supplemented by surgical audit database and patients' electronic medical record. Results: There were 31 bile leaks amongst 639 patients with blunt liver trauma (4.9%). Bile leak was associated with higher liver injury grade (odds ratio (OR) 36, P  = 0.001), hepatic embolization (OR 16, P  = 0.003) and need for trauma laparotomy (OR 14, P  = 0.024). ERCP was performed in 58.1% ( n  = 18). This was complicated in 27.7% ( n  = 5) by mild pancreatitis ( n  = 1) and intra‐abdominal sepsis ( n  = 4) requiring surgical drainage of abscess ( n  = 2) and liver resection ( n  = 1). Bile leak settled conservatively (including percutaneous drainage) without ERCP in the remaining patients (41.9%). Overall mortality was not increased in those with bile leak ( P  = 0.998). Conclusion: Bile leaks resolved conservatively in 41.9% of patients. Complications following ERCP were seen in 27.7%, frequently requiring intervention. Failure of conservative management was more likely in patients with hepatic embolization, in whom early ERCP remains appropriate. ERCP should otherwise be reserved for those who fail conservative management to minimize infective complications. Abstract : Incidence of bile leak post blunt liver trauma in our cohort over 10 years is 4.9%. Bile leaks resolved without endoscopic retrograde pancreaticocholangiography ( ERCP) in 41.9%. Complications following ERCP is seen in 27.7%, frequently requiring intervention for infectious complications. ERCP should be reserved for those who fail conservative management to avoid infectious complications. However, early ERCP remains appropriate for those with prior hepatic embolization or proximal bile leak where it is unlikely to settle conservatively.